Classification and relationships of Assiculus and Assiculoides (Teleostei: Pseudochromidae) - Gill, Anthony C. (Zootaxa, 2013)
The monotypic Australian pseudochromid fish genera Assiculus and Assiculoides had been previously included in the subfamily Pseudochrominae on the basis of symplesiomorphic characters. Osteological synapomorphies are identified in support of a closer relationship to the remaining pseudochromid subfamilies. Two synapomorphies (five or fewer infraorbital bones, haemal spine of preural vertebra 2 attached to centrum) diagnose a clade consisting of Assiculoides, Pseudoplesiopinae, Anisochrominae and Congrogadinae. Two additional synapomorphies (parhypural not separate from hypurals 1+2, total caudal-fin rays modally 27 or fewer) diagnose a more inclusive clade that also includes Assiculus. Two new subfamilies are erected to reflect these relationships.